HISTORY OF RESIDENTIAL COMPLEXES IN THE CITY OF TASHKENT AND MODERN TRENDS IN THEIR DESIGN - Sereyeva Guljazira Adilbaevna; Abrorova Nigina Nodir qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Abstract: This article examines the history of residential complexes in Tashkent, covering several stages, each reflecting various socioeconomic and architectural processes occurring in the city and current trends in residential complex design, reflecting changing demands on the urban environment and social needs. Particular attention is paid to key aspects such as the flexibility and adaptability of spaces, environmental sustainability, the integration of high technologies, and social and public integration. It concludes that modern residential complexes strive to create a sustainable and comfortable urban environment capable of adapting to change and meeting the needs of residents.